Answer:
The equation
represents the valid step in solving the given expression ![\sqrt[3]{2x-6}+\sqrt[3]{2x+6}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B2x-6%7D%2B%5Csqrt%5B3%5D%7B2x%2B6%7D)
Therefore the option ![(\sqrt[3]{2x-6})^3=(-\sqrt[3]{2x+6})^3](https://tex.z-dn.net/?f=%28%5Csqrt%5B3%5D%7B2x-6%7D%29%5E3%3D%28-%5Csqrt%5B3%5D%7B2x%2B6%7D%29%5E3)
Step-by-step explanation:
Given expression is ![\sqrt[3]{2x-6}+\sqrt[3]{2x+6}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B2x-6%7D%2B%5Csqrt%5B3%5D%7B2x%2B6%7D)
To solve the given expression as below :
![\sqrt[3]{2x-6}+\sqrt[3]{2x+6}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B2x-6%7D%2B%5Csqrt%5B3%5D%7B2x%2B6%7D)
![\sqrt[3]{2x-6}=-\sqrt[3]{2x+6}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B2x-6%7D%3D-%5Csqrt%5B3%5D%7B2x%2B6%7D)
cubing on both sides we get
![(\sqrt[3]{2x-6})^3=(-\sqrt[3]{2x+6})^3](https://tex.z-dn.net/?f=%28%5Csqrt%5B3%5D%7B2x-6%7D%29%5E3%3D%28-%5Csqrt%5B3%5D%7B2x%2B6%7D%29%5E3)
The equation
represents the valid step in solving the given expression ![\sqrt[3]{2x-6}+\sqrt[3]{2x+6}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B2x-6%7D%2B%5Csqrt%5B3%5D%7B2x%2B6%7D)
Therefore the option ![(\sqrt[3]{2x-6})^3=(-\sqrt[3]{2x+6})^3](https://tex.z-dn.net/?f=%28%5Csqrt%5B3%5D%7B2x-6%7D%29%5E3%3D%28-%5Csqrt%5B3%5D%7B2x%2B6%7D%29%5E3)
Answer:
5%
Step-by-step explanation:
We know that when there are four people, then each person gets 25% of the halwa. However, when the fifth person comes, they have everyone including the guest get 20% of the halwa. In this way, the original four people are losing 5% of their halwa in order for the fifth person to get his piece
B. 8 inches, hope this was right and helped:)
Hello,
x²+6x-7=0
==>x²+2*3x+3²-9-7=0
==>(x+3)²-16=0
Answer D